Closed Venereology Wards in the German Democratic Republic - Florian Steger; Maximilian Schochow (Acta Medico-Historica Rigensia, 2019)
Over the 40-year existence of the German Democratic Republic (GDR), multiple thousands of women have been committed to closed venereology wards. The system of compulsory hospitalisation to closed venereology wards established in the GDR was based on the Soviet healthcare system. Its purpose was not simply to sanction behavior that diverged from the prescribed socialist norm but also to educate women in accordance with socialist standards. The involuntarily committed women in the GDR were treated by measures of politicised medicine. This medicine was shaped and executed by actors who imposed their own standards on the victimised women daily. Moreover, all closed venereology wards in the GDR were monitored by the Ministry of State Security through a network of inofficial informants.